Speech Outcomes after Delayed Hard Palate Closure and Synchronous Secondary Alveolar Bone Grafting in Patients with Cleft Lip, Alveolus and Palate - Haj, Mona; Hakkesteegt, S.N.; Poldermans, H.G.; de Gier, H.H.W.; Versnel, S.L.; Wolvius, E.B. (Archives of Plastic Surgery, 2024)
Background The best timing of closure of the hard palate in individuals with cleft lip, alveolus, and palate (CLAP) to reach the optimal speech outcomes and maxillary growth is still a subject of debate. This study evaluates changes in compensatory articulatory patterns and resonance in patients with unilateral and bilateral CLAP who underwent simultaneous closure of the hard palate and secondary alveolar bone grafting (ABG).Methods A retrospective study of patients with nonsyndromic unilateral and bilateral CLAP who underwent delayed hard palate closure (DHPC) simultaneously with ABG at 9 to 12 years of age from 2013 to 2018. The articulatory patterns, nasality, degree of hypernasality, facial grimacing, and speech intelligibility were assessed pre- and postoperatively.Results Forty-eight patients were included. DHPC and ABG were performed at the mean age of 10.5 years. Postoperatively hypernasal speech was still present in 54% of patients; however, the degree of hypernasality decreased in 67% (p < 0.001). Grimacing decreased in 27% (p = 0.015). Articulation disorders remained present in 85% (p = 0.375). Intelligible speech (grade 1 or 2) was observed in 71 compared with 35% of patients preoperatively (p < 0.001).Conclusion This study showed an improved resonance and intelligibility following DHPC at the mean age of 10.5 years, however compensatory articulation errors persisted. Sequential treatments such as speech therapy play a key role in improvement of speech and may reduce remaining compensatory mechanisms following DHPC.
Keywords: cleft lip with or without cleft palate; cleft palate; speech; hard palate closure; alveolar bone grafting